Otoritas Barakka: Kepemimpinan Kiai di Pesantren Sulawesi Selatan dalam Tradisi Bugis - Andy Andy; Akramun Nisa; Khaerunnisa Khaerunnisa; Sitti Nadirah; Ali Rahman (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2026)
Pesantren in Indonesia have long demonstrated remarkable institutional resilience amid the pressures of modernization, yet the sources of this resilience remain inadequately theorized in conventional educational management literature. This study investigates how Barakka authority — a concept of divine blessing and moral legitimacy rooted in the Bugis-Islamic tradition of South Sulawesi — shapes and sustains the institutional resilience of Pondok Pesantren DDI Mangkoso. Employing Interpretive Phenomenological Analysis as both an epistemological foundation and methodological design, data were collected through in-depth interviews, three months of participatory observation, and institutional document analysis. Findings reveal that Barakka authority operates across five governance dimensions: human resource management framed through the principle of amanah, curriculum renewal through spiritually grounded ijtihad, financial trust rooted in the inherited institutional Barakka, digital transformation legitimized as wasilah, and strategic network expansion curated on the basis of shared Islamic values. These findings demonstrate that deep spiritual commitment and high institutional professionalism are not opposing forces but mutually reinforcing ones, when integrated through community-recognized Barakka-based leadership. This study proposes Barakka authority as a distinct construct that extends Weber's charismatic typology while offering an indigenous Islamic governance framework with broader implications for faith-based educational leadership beyond the Indonesian context.